Feasibility of using mobile point-of-sale technology in Baltimore City corner stores tracking sales: A brief report - Emma C. Lewis; Kaitlyn M. Harper; Lisa K. Poirier; Joel Gittelsohn (SAGE Publishing, 2021)
Small food retail stores in many underserved urban settings keep no electronic records, making documentation of program impact on sales difficult to obtain. We examined the feasibility of introducing a point-of-sale tablet (POST) application to track sales of foods and beverages in Baltimore City corner stores. A sample of four geographically and ethnically diverse corner store owners were trained to use POST to track sales of 14 items for eleven days. Feasibility was documented via a structured survey and open-ended interviews. POST had high economic and cultural acceptability, operability, and perceived sustainability, regardless of language differences or familiarity with mobile technology. All store owners reported willingness to use POST again. It is feasible to train corner store owners to use a point-of-sale application for sales monitoring. An upcoming trial will help to ensure that POST provides sufficient value added for corner store owners.